2013
DOI: 10.1186/1756-0500-6-375
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin protection activities against γ-Rays-induced molecular and biochemical lesions

Abstract: BackgroundCurcumin is a yellow-pigment phenolic compound used as a food spice and has a broad spectrum of antioxidant, anti-carcinogenic, anti-mutagenic and anti-inflammatory properties.MethodsRadio-protective efficacy of curcumin; diferuloylmethane (C21H20O6) was evaluated using molecular and biochemical assays in male mice after exposure to 3 Gy γ-rays. Curcumin was given at a dose of 400 μmol/ kg body weight via gastric tubes for 5 following days either pre-, post- or both pre- and post-exposure.ResultsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…It is known that exposure to irradiation induces liver damage (El-Gazzar et al 2016;Khattab et al 2017;Ashry et al 2017;Radwan and Mohamed 2018;). It is also reported that γ-radiation causes multiple organ dysfunction especially in the liver and an increase of MDA levels in various tissues depending on the time and dose (Simsek et al 2012;Tawfik et al 2013;Xie et al 2014;El-Gazzar et al 2016). In this study, γ-radiation caused a significant increase in MDA in the kidney and brain tissues together with the liver but a non-significant increase in the heart, spleen and ovary tissues.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It is known that exposure to irradiation induces liver damage (El-Gazzar et al 2016;Khattab et al 2017;Ashry et al 2017;Radwan and Mohamed 2018;). It is also reported that γ-radiation causes multiple organ dysfunction especially in the liver and an increase of MDA levels in various tissues depending on the time and dose (Simsek et al 2012;Tawfik et al 2013;Xie et al 2014;El-Gazzar et al 2016). In this study, γ-radiation caused a significant increase in MDA in the kidney and brain tissues together with the liver but a non-significant increase in the heart, spleen and ovary tissues.…”
Section: Discussionsupporting
confidence: 54%
“…Being a major bioactive compound in turmeric, curcumin is a yellow pigment phenolic compound obtained from the roots of turmeric used as spice. It has a wide spectrum of anti-oxidant, anti-carcinogenic, anti-mutagenic, and anti-inflammatory properties (Tawfik et al 2013).…”
mentioning
confidence: 99%
“…65 However, It enhances NK cell-induced apoptosis in pancreatic cancer cells (Fiala, 2015) and inhibits interferon-γ production. 34,66 Additionally, curcumin reduces the hepatotoxicity induced by arsenic, cadmium, chromium, copper, lead and mercury, prevents histological injury, lipid peroxidation and glutathione (GSH) depletion, maintains the liver antioxidant enzyme status and protects against mitochondrial dysfunction. 67 Trans (t)-resveratrol (3,4,5-trihydoxystilbene), present naturally in grapes and other fruits, induces Cdc2-tyr15 phosphorylation via ATM/ ATR-Chk1/2-Cdc25C pathway considered as a central mechanism for S phase arrest in human ovarian carcinoma Ovcar-3 cells.…”
Section: Other Phenolic Compoundsmentioning
confidence: 99%
“…In the same direction, Sankar et al (2014) support protective effects of curcumin on genotoxic effects exerted by Arsenic in bone marrow cells through attenuation of its drawbacks on chromosomal aberrations, micronuclei formation and DNA damage. Tawfik et al (2013) studied protective effects of curcumin on irradiated mice and found that it had significant radioprotective and radio-recovery activities. Malhotra et al (2012) reported that combined treatment with curcumin and resveratrol stimulate apoptosis and hence, they modulates mitotic injury in benzo(a)pyrenetreated mice.…”
Section: In Vitro Effects Of Phenytoin (Pht) and Pht + S9 On The Isolmentioning
confidence: 99%